Fbxo16 mediates degradation of NF-κB p65 subunit and inhibits inflammatory response in dendritic cells - Sugimoto-Ishige, Akiko; Jodo, Aya; Tanaka, Takashi (Frontiers in Immunology, 2025)
Activation of transcription factor NF-κB is tightly regulated by negative regulatory systems that prevent excessive inflammation leading to autoimmune diseases. We previously demonstrated that PDLIM2, a PDZ-LIM domain-containing nuclear protein, functions as a ubiquitin E3 ligase that targets the p65 subunit of NF-κB and STAT3/STAT4 transcription factors for proteasomal degradation, thus terminating immune responses in dendritic cells and CD4+T cells, respectively. In this study, we have demonstrated that PDLIM2 forms a ubiquitin ligase complex with Cullin 1, a scaffold protein, providing a platform consisting of complex and Skp1, an adaptor protein. Moreover, by screening using siRNA for F-box-containing proteins, we have identified Fbxo16 as a substrate-recognition receptor for p65 in this complex. Fbxo16 bound to p65 and promoted its polyubiquitination and degradation, thereby suppressing NF-κB transactivation. Consistently, Fbxo16 deficiency in dendritic cells resulted in a larger amount of nuclear p65 and thus enhanced production of proinflammatory cytokines. On the other hand, Fbxo16 could not promote the degradation of STAT3 or STAT4, and Fbxo16 deficiency did not affect STAT3- and STAT4-mediated immune responses of CD4+T cells. These results delineate a role of Fbxo16, as a substrate receptor for p65 in a PDLIM2-containing ubiquitin ligase complex, in negatively regulating NF-κB-mediated inflammatory responses in dendritic cells.